Розпаралелювання алгоритмів відеопотоку в платформі Каскада - Бржескі, Адам (Видавництво Львівської політехніки, 2011)
The purpose of this work is to present different techniques of video stream algorithms parallelization provided by the Kaskada platform - a novel system working in a supercomputer environment designated for multimedia streams processing. Considered parallelization methods include frame-level concurrency, multithreading and pipeline processing. Execution performance was measured on four time-consuming image recognition algorithms, designed to support medical endoscopic examinations. The achieved results confirm high capabilities of Kaskada platform for executing parallel algorithms. Frame-level parallelization was proved to be a great solution for offline processing, while pipeline processing combined with multithreading provided high performance for online, real-time analysis.
Keywords: parrallel processing; pipeline processing; multithreading; high-performance computing; endoscopy